Fundamentals of cost accounting - Maher, Michael W. (McGraw Hill, 2006)
A direct, realistic, and efficient way to learn cost accounting. Fundamentals is short (608 pages) making it easy to cover in one semester. The authors have kept the text concise by focusing on the key concepts students need to master. Opening vignettes and In Action boxes show realistic applications of these concepts throughout. Comprehensive end-of-chapter problems plus Homework Manager provide students with all the practice they need to fully learn each concept.